Porous monoliths of 3D graphene for electric double‐layer supercapacitors. Issue 2 (17th March 2021) - Zeng, Jinjue; Xu, Chenyang; Gao, Tian; Jiang, Xiangfen; Wang, Xue‐Bin
Abstract: For delivering the nanoscaled extraordinary characteristics in macroscopical bulk, it is essential to integrate two‐dimensional nanosheets into three‐dimensional (3D) porous monoliths, alternatively called as 3D architectures, 3D networks, or aerogels. The intersupported structure of porous monolithic 3D graphene (3DG) can prevent aggregation or restacking of graphene individuals, and the interconnected sp 2 network of 3DG not only can provide the highway for the transport of electron/phonon but also can present continual cavities/channels for mass transfer. This review summarizes the synthesis methodology of 3DG porous monoliths and highlights the application for electric double‐layer capacitors. Present challenges and future prospects about the manufacture and application of 3DG are also discussed. Abstract : This review provides recent advances and strategies on syntheses of three‐dimensional graphene (3DG) porous monoliths, including liquid‐based assembly, chemical vapor deposition, and pyrolysis of solid/liquid carbon sources. Electric double‐layer capacitor applications of 3DG are also summarized.